1995
DOI: 10.1007/bf00191816
|View full text |Cite
|
Sign up to set email alerts
|

An intragenic TaqI polymorphism in the faciogenital dysplasia (FGD1) locus, the gene responsible for Aarskog syndrome

Abstract: A Taq1 polymorphism, located in intron 4 of the faciogenital dysplasia (FGD1) gene, the gene responsible for Aarskog syndrome, is described. FGD1 encodes a putative Rho/Rac guanine nucleotide exchange factor involved in mammalian morphogenesis. The identification of an intragenic polymorphism will facilitate the accurate carrier detection of individuals at risk for Aarskog syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…One example is FGD1, a GEF of Cdc42 shown originally to be localized to patches underlying the plasma membrane as well as at the Golgi [ 28 ]. Mutations in the FGD1 gene are linked to the rare disease faciogenital dysplasia, and it was this observation that first drew attention to its possible role in the cell [ 55 ]. It was subsequently shown that the FGD1 protein localizes to the TGN and that its depletion results in reduced transport of VSV-G cargo between the TGN and cell surface.…”
Section: Regulation Of Golgi-associated Membrane Trafficking Events By Rho Proteinsmentioning
confidence: 99%
“…One example is FGD1, a GEF of Cdc42 shown originally to be localized to patches underlying the plasma membrane as well as at the Golgi [ 28 ]. Mutations in the FGD1 gene are linked to the rare disease faciogenital dysplasia, and it was this observation that first drew attention to its possible role in the cell [ 55 ]. It was subsequently shown that the FGD1 protein localizes to the TGN and that its depletion results in reduced transport of VSV-G cargo between the TGN and cell surface.…”
Section: Regulation Of Golgi-associated Membrane Trafficking Events By Rho Proteinsmentioning
confidence: 99%
“…An intragenic Taq I restriction site FGD1 polymorphism [Pasteris and Gorski, 1995] and four microsatellite markers anking the FGD1 gene were investigated in this family (Fig. 3).…”
Section: Molecular Studymentioning
confidence: 99%